Organization experience of diagnostic and medicosocial services for patients with Charcot—Marie—Tooth disease in Krasnoyarsk region - E. V. Glushchenko; N. A. Shnayder; E. A. Kantimirova; E. A. Kozulina; M. I. Voevoda; V. N. Maksimov; A. A. Allakhverdyan (Нервно-мышечные болезни, 2015)
Hereditary neuropathy Charcot-Marie-Tooth (CMT) is the most common form of hereditary polyneuropathies. Goal of the study was the development of evidence-based diagnostic and treatment algorithms using patients with CMT (for example, in Krasnoyarsk Territory).Materials and methods: A total of 324 people. (probands and their relatives 1 and 2 lines of kinship). We analyzed 125 (38,5 %) clinical cases of CMT, 64/125 (51,2 %) clinical cases were include to statistical analysis (probands and their family trees, past the full range of clinical and laboratory findings according to the protocol this study). Age ranged from 6 to 81 years, median age — 30,5 years, including women 24 (37,5 %), median age — 33,5 years; males 40 (62,5 %), median age — 28,5 years. Methods of diagnosis: clinical, genetic, neurophysiological, molecular genetic, assessment of quality of life assessment of anxiety and depression.Results: The family history of CMT noted in 53/57 (93,0 %) cases, with a predominance of autosomal dominant type of inheritance —52 (91,2 %) cases. As a result of DNA testing duplication of peripheral myelin protein gene (RMR22) on chromosome 17, held 34 survey, this mutation was found in 17 (50,0 %) patients. Modified method of computer esthesiometry for CMT diagnosis using domestic diagnostic equipment “Vibrotester-MBN” BT-02-1 has a high sensitivity in the early stages of the disease and can be recommended for more widespread adoption of on par with other subjects of the Russian Federation.